Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Komitmen Organisasi dalam Meningkatkan Kinerja Pegawai pada Badan Perencanaan Pembangunan Kabupaten Bungo - Leni Elvira; Saiyid Syekh; Sudirman Sudirman (Universitas Batanghari, 2023)
This research aims to find out and describe the condition of leadership style, organizational culture and employee performance at BAPPEDA Bungo. And to determine the influence of leadership style and organizational culture through organizational commitment on employee performance. This research was carried out at BAPPEDA Bungo Regency. This research uses path analysis with the census method. The results of this research are (1) leadership style has a partial and significant effect on employee organizational commitment. (2) organizational culture has a partial and significant effect on employee organizational commitment. (3) leadership style and organizational culture have a joint and significant effect on employee organizational commitment. (4) then leadership style has a partial and significant effect on employee performance. (5) competency has a partial and significant effect on employee performance. (6) leadership style and organizational culture have a joint and significant effect on employee performance. (7) organizational commitment has a partial and significant effect on employee performance. (8) partial leadership has no significant effect on employee performance (9) partial organizational culture has no significant effect on employee organizational performance (10) organizational commitment has a significant effect on employee organizational performance (11) Leadership Style, Organizational Culture and Organizational Commitment together -the same has a significant effect on employee performance